Monoamine Oxidase A and B Gene Polymorphisms and Negative and Positive Symptoms in Schizophrenia. (19th April 2012) - Camarena, Beatriz; Fresán, Ana; Aguilar, Alejandro; Escamilla, Raúl; Saracco, Ricardo; Palacios, Jorge; Tovilla, Alfonso; Nicolini, Humberto
Abstract : Given that schizophrenia is a heterogeneous disorder, the analysis of clinical characteristics could help to identify homogeneous phenotypes that may be of relevance in genetic studies. Linkage and association studies have suggested that a locus predisposing to schizophrenia may reside within Xp11. We analyzed uVNTR and rs1137070, polymorphisms from MAOA and rs1799836 of MAOB genes to perform single SNP case-control association study in a sample of 344 schizophrenia patients and 124 control subjects. Single polymorphism analysis of uVNTR, rs1137070 and rs1799836 SNPs did not show statistical differences between cases and controls. Multivariate ANOVA analysis of clinical characteristics showed statistical differences between MAOB /rs1799836 and affective flattening scores (F = 4.852, P = 0.009 ), and significant association between MAOA /uVNTR and affective flattening in female schizophrenia patients (F = 4.236, P = 0.016 ) after Bonferroni's correction. Our preliminary findings could suggest that severity of affective flattening may be associated by modifier variants of MAOA and MAOB genes in female Mexican patients with schizophrenia. However, further large-scale studies using quantitative symptom-based phenotypes and several candidate variants should be analyzed to obtain a final conclusion.